Advanced gastrointestinal carcinoma with massive ascites and hydrothorax during pregnancy: A case report and review of the literature. Issue 51 (December 2017) - Ye, Wenfeng; Tang, Yanhong; Yao, Changfang; Shi, Junyu; Xu, Yongjuan; Jiang, Jingting
Abstract: Rationale: Gastrointestinal carcinoma is rare during pregnancy. It is usually diagnosed at an advanced stage because special gastrointestinal symptoms are generally overlooked during pregnancy, and there are many limitations and contraindications for using diagnostic tools during pregnancy. Patient concerns: We present a case of a 29-year-old patient with 27 weeks and 5 days of gestation due to massive ascites and hydrothorax. Diagnoses: The patient was diagnosed with an advanced gastrointestinal cancer. Pathological report showed poorly differentiated tumor with the signet ring cell component. Interventions: Caesarean section was performed. At the same time, an abdominal exploration showed that the omentum was like biscuits . There were extensive and firm intestinal adhesions, and many tumor lesions were found on the surface of greater curvature of stomach, spleen, intestine, peritoneum, ascending colon and descending colon. Outcomes: Gastrointestinal surgeon was invited during operation, and palliative gastrectomy was not performed because of extensive metastases. The patient died 30 days after caesarean section. Lessons: This study present a case with advanced gastrointestinal cancer during pregnancy. We suggest that endoscopic exam is recommended if the patient is highly suspicious.